Energi Listrik dari Pengereman Regeneratif Sepeda Motor dengan Menggunakan Dinamo Sepeda - Melda Latif; Anugrah Valdesio; Mumuh Muharam (Jurusan Teknik Elektro Universitas Andalas, 2018)
Regenerative breaking is an energy recovery mechanism from wasted energy during breaking process. In a conventional breaking process, the kinetic energy from the wheel is converted into heat due to friction of the break disc. In regenerative breaking, the kinetic energy is converted into electric energy by a dynamo. This research aims to find amount of electric power, voltage and current that can be generated from regenerative breaking. By adding a prototype which contains dynamo of bicycle, rectifier and dc-dc converter, the generative braking can change kinetic energy into electrical energy. In this research, three types of front wheel disc, i.e. with hard insulation, soft insulation and without insulations had been used for the experiment.. It is found that the best result is obtained by using hard insulation. For motorcycle speed at 70 km/hours, voltage, current and power values are 12,8 Volt, 130 mA and 1664 mWatt. The advantages of the hard insulation are less friction, less heat dissipation and quieter. Keywords : Regenerative braking, motorcycle, isolation, wheel, dynamo of bicycle.